The physics of solar energy conversion - Bisquert, Juan (Boca Raton : CRC Press, 2020)
"The conceptual picture of a solar cell has evolved in the last two decades, a broad landscape of candidate materials and devices were discovered and systematically studied and reported. New concepts and a rather powerful picture embracing very different types of devices has emerged from many discussions and sometimes also conceptual clashes. This handbook introduces the main physico-chemical principles that govern the operation of energy devices. The work presents an explanation of the operation of photovoltaic devices with a broad perspective that embraces concepts from nanostructured and highly disordered materials to highly efficient devices such as lead halide perovskite solar cells"--
Introduction to energy devices -- Electrostatic and thermodynamic potentials of electrons in materials -- Voltage, capacitors, and batteries -- Work functions and injection barriers -- Thermal distribution of electrons, holes, and ions in solids -- Interfacial kinetics and hopping transitions -- The chemical capacitance -- The density of states in disordered inorganic and organic conductors -- Planar and nanostructured semiconductor junctions -- Carrier injection and drift transport -- Diffusion transport -- Drift-diffusion transport -- Transport in disordered media -- Thin film transistors -- Space-charge-limited transport -- Impedance and capacitance spectroscopies -- Blackbody radiation and light -- Light absorption, carrier recombination, and luminescence -- Optical transitions in organic and inorganic semiconductors -- Fundamental model of a solar cell -- Recombination current in the semiconductor diode -- Radiative equilibrium in a semiconductor -- Reciprocity relations in solar cells and fundamental limits to the photovoltage -- Charge separation and material limits to the photovoltage -- Operation of solar cells and fundamental limits to their performance -- Charge collection in solar cells -- Solar energy conversion concepts.
OCLC-licensed vendor bibliographic record.
Keywords: Solar cells; SCIENCE / Chemistry / General; SCIENCE / Physics; TECHNOLOGY / Material Science